PENERAPAN MODEL PEMBELAJARAN KOOPERATIFPENDEKATAN STRUKTURAL THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJARMATEMATIKA PESERTA DIDIK KELAS VIIIF SMP NEGERI 18 PEKANBARU - Sari Mardisa Putri; Jalinus Jalinus; Sakur Sakur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract This research aims to improve mathematics achievement in SMP N 18Pekanbaru by implement cooperative learning model approach to structural Think Pair Square. Subjectswere studentsgrade VIIIFwhohave theacademicability oftheheterogeneous. This research is aclass action research with twocycles. Each a cyclehas fourstages, thestagesareplanning, action, observation, andreflection. The results showed the activity of teachers and learners have done well after doing the action. An increase in the number of students who achieved at UH KKM end of each cycle compared to the number of students who achieve KKM on base score, the number of students who scored 20 and 30 more than to the development of the number of students who received grades 5 and 10. As well as the increase in the value of the mean, median and mode learners from the first cycle to the second cycle. Conclusion of this study indicate that the application of cooperative learning model TPS Structural Approaches canimprove the mathematics achievement of learners grade VIIIF SMP Negeri 18 Pekanbaru in the first semester academic year2013/2014. Keywords: Mathematics learning outcome, Cooperative learning, Think Pair Square, Class action research